Dissolved Inorganic and Organic Carbon in an Ephemeral Fresh Water Stream in Southern Arizona. Issue 5 (October 2019) - Jull, A J Timothy; Burr, George S; Leonard, Alexander G; Fitzgerald, Jamie; Cheng, Li; Cruz, Richard; Biddulph, Dana
ABSTRACT: We report on an initial long-term study of dissolved inorganic and organic carbon (DIC) from Sabino Creek, located in Sabino Canyon, Pima County, Arizona. The purpose of this study was to monitor changes in dissolved radiocarbon ( 14 C) with time and to understand the processes contributing to these variations. Our results span the period 2009–2016 and show a mixing trend between dissolved inorganic and organic carbon modern end-members with an older component. This study provides preliminary information for more detailed research on recycling of organic components in this stream system.